2023
DOI: 10.1186/s12967-023-04430-x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the biology and development of lung cancer in never smokers—implications for early detection and treatment

Peiyao Wang,
Sophie Sun,
Stephen Lam
et al.

Abstract: Lung cancer is the leading cause of cancer deaths worldwide. Despite never smokers comprising between 10 and 25% of all cases, lung cancer in never smokers (LCNS) is relatively under characterized from an etiological and biological perspective. The application of multi-omics techniques on large patient cohorts has significantly advanced the current understanding of LCNS tumor biology. By synthesizing the findings of multi-omics studies on LCNS from a clinical perspective, we can directly translate knowledge re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 113 publications
2
2
0
Order By: Relevance
“…RF-predicted FS classes also showed a divide in mutational signature profiles, where CS-like FS had relatively greater levels of tobacco mutagen signature SBS4 and NS-like FS had relatively higher levels of endogenous signatures SBS1, SBS6, and SBS2. These trends have been previously reported in true CS and NS patients with LUAD, respectively, supporting a clear and biologically relevant subdivision within FS [ 25 ].…”
Section: Discussionsupporting
confidence: 85%
“…RF-predicted FS classes also showed a divide in mutational signature profiles, where CS-like FS had relatively greater levels of tobacco mutagen signature SBS4 and NS-like FS had relatively higher levels of endogenous signatures SBS1, SBS6, and SBS2. These trends have been previously reported in true CS and NS patients with LUAD, respectively, supporting a clear and biologically relevant subdivision within FS [ 25 ].…”
Section: Discussionsupporting
confidence: 85%
“…As in prior LCINS studies 10 , EGFR and TP53 harbored the most driver mutations, with 52.2% and 30.5% mutated in adenocarcinomas, respectively, whereas KRAS was only mutated in 6.5% of samples. EGFR and TP53 mutations were enriched in patients from East Asia, as previously reported 35 , and KRAS mutations were elevated in North American and European patients ( Fig.…”
Section: Resultssupporting
confidence: 69%
“…The prevalence of lung cancer in never smokers (LCINS) varies by several notable factors, namely enrichment in females 4 , Asian populations 5 , and individuals with a family history of lung cancer 6 . The occurrence of LCINS can also differ by geographic regions, with higher rates reported in East Asia 7,8 and Eastern Europe 9 when compared to countries in North America and Western Europe 10 . Epidemiological studies have also identified environmental exposures that can increase LCINS risk, including exposure to secondhand smoke 11 and air pollution 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, men's smoking prevalence and cumulative smoking exposure are generally higher than women's, and men's smoking cessation rate is lower, which is also an important reason why men have a higher incidence of lung cancer than women [5] . However, the incidence of lung cancer in non-smokers still exists and may be increasing in certain regions and populations [6][7][8] . The research by REVEL M and colleagues indicates that in most European countries, it is anticipated that the mortality rate from lung cancer in females will surpass that of breast cancer [9] .…”
Section: Introductionmentioning
confidence: 99%